Involvement of the M-CSF/IL-34/CSF-1R pathway in malignant pleural mesothelioma - Blondy, Thibaut (J Immunother Cancer, 2020)
BACKGROUND: Malignant pleural mesothelioma (MPM) is a rare and aggressive cancer related to asbestos exposure. The tumor microenvironment content, particularly the presence of macrophages, was described as crucial for the development of the disease. This work aimed at studying the involvement of the M-CSF (CSF-1)/IL-34/CSF-1R pathway in the formation of macrophages in MPM, using samples from patients. METHODS: Pleural effusions (PEs), frozen tumors, primary MPM cells and MPM cell lines used in this study belong to biocollections associated with clinical databases. Cytokine expressions were studied using real-time PCR and ELISA. The Cancer Genome Atlas database was used to confirm our results on an independent cohort. An original three-dimensional (3D) coculture model including MPM cells, monocytes from healthy donors and a tumor antigen-specific cytotoxic CD8 T cell clone was used. RESULTS: We observed that high interleukin (IL)-34 levels in PE were significantly associated with a shorter survival of patients. In tumors, expression of CSF1 was correlated with ‘M2-like macrophages’ markers, whereas this was not the case with IL34 expression, suggesting two distinct modes of action of these cytokines. Expression of IL34 was higher in MPM cells compared with primary mesothelial cells. Particularly, high expression of IL34 was observed in MPM cells with an alteration of CDKN2A. Finally, using 3D coculture model, we demonstrated the direct involvement of MPM cells in the formation of immunosuppressive macrophages, through activation of the colony stimulating factor-1 receptor (CSF1-R) pathway, causing the inhibition of cytotoxicity of tumor antigen-specific CD8(+) T cells. CONCLUSIONS: The M-CSF/IL-34/CSF-1R pathway seems strongly implicated in MPM and could constitute a therapeutic target to act on immunosuppression and to support immunotherapeutic strategies.